Proceedings of the 1985 meeting of West Indies sugar technologists ([Sugar Association of the Caribbean] [Port-of Spain]TT, 1985)
Papers discuss application of technology to a variety of field and factory activities in the Caribbean sugar industry. Gives perspectives on the present and future of sugar as a sweetener. Discusses inter alia, applications of computers to the sugar industry; soils and water; cane varieties; distillery management; research and experiments in specific areas in different territories; agricultural diversification; the use of mechanical harvesters; weed and disease control; the harvesting period; and juice analysis.
Includes bibliographies. 2 v.